Assessment of Clinical Nurses’ Proficiency in Wound Management of Patients with Diabetes at Kubwa General Hospital in Abuja, Nigeria - Olaolorunpo Olorunfemi; Michael Jacob; Oluseyi Adetunmise Olajide (APIK Journal of Internal Medicine)
Background: Assessing clinical nurses’ wound management skills for diabetic patients is crucial for providing high-quality care. Improper handling of diabetes care can have serious repercussions, including foot sores or leg amputations. Aim: The aim of this study was to assess clinical nurses’ competency in diabetes wound care. Materials and Methods: A descriptive cross-sectional study design was chosen. Self-administered, content-validated questionnaires and observational checklists were used to gather data on clinical nurses’ proficiency on wound management. Convenience sampling was used to select 127 nurses as a representative sample. The Statistical Program for Social Sciences (SPSS) version 23.0 was utilized for data analysis, and Pearson’s Chi-square test (0.05) was employed to conduct an inferential analysis with a significance level of 5%. Results: In this study, 35.4% of respondents were between the ages of 38 and 47; 70.1% were females, and 55.2% were married. Approximately 31.5% of the population were registered nurses, while 28.3% had a bachelor’s degree in nursing. Remarkably, 37% of those surveyed also work in hospital surgical wards, and 95.2% of them have extensive understanding of diabetic patient wound care. The majority of the participants attest that there is not enough time to provide diabetics patients with thorough wound care. In addition, 36.2% of nurses accurately record the wound’s features during the assessment and dressing steps. However, the ground mean of clinical nurses’ proficiency in diabetics patients’ wound management was found to be average with X̅ = 2.79, standard deviation = 1.306. Moreover, a noteworthy correlation has been observed between the proficiency of clinical nurses in wound care and their corresponding experience levels (χ2 = 23.62, df = 4, and P ˂ 0.05). Conclusions: We found an average degree of proficiency and competency among clinical nurses. The study suggests that regular training, workshops, and evaluations be held, and that diabetes wound care is included in the nursing curriculum.